Radiation dose measurement for patients undergoing nuclear medicine diagnostic studies and for medical staff - Usongtham, Parita; Awikunprasert, Panatsada (Journal of Medicine and Health Sciences, 2024)
Nuclear medicine tests involve injecting radioactive substances into the patient's body to provide information about organ function and pathology. This raises concerns about radiation safety when managing or caring for patients exposed to radiation. The objective of this study was to measure the radiation dose rate emitted by patients during various nuclear medicine diagnostic tests. A gas-filled dosimeter was used to measure the radiation dose rate at three key times: immediately after the radiopharmaceutical injection, during the nuclear medicine examination, and before the patient was discharged. Measurements were taken at distances of 0, 0.25, 0.5, 1, and 2 meters from the patient. The study involved 385 patients undergoing 21 different nuclear medicine examinations. Six types of examinations exhibited an average radiation dose rate higher than 10 µSv/hr at 0 meters immediately after radiopharmaceutical injection. During the examination, five types of tests showed similar rates, and before discharge, only two types did. The highest radiation dose rate, observed immediately after injection during a PET/CT scan, reached 248 µSv/hr. This rate decreased during subsequent examinations and before the patients were discharged. The radiation dose rate consistently diminished as the distance from the patient increased. Notably, no examination recorded a radiation dose rate exceeding 50 µSv/hr at a distance of 1 meter from the patient before discharge. In conclusion, nuclear medicine diagnostic tests involve the use of radioactive tracers, leading to the highest radiation dose rates immediately after injection, which then decrease over time and distance. These radiation levels remain within safe limits for both medical staff and patients.